Trends in antimicrobial resistance in Neisseria gonorrhoeae in the USA: the Gonococcal Isolate Surveillance Project (GISP), January 2006–June 2012. (15th November 2013) - Kirkcaldy, Robert D; Kidd, Sarah; Weinstock, Hillard S; Papp, John R; Bolan, Gail A
Abstract : Background: Neisseria gonorrhoeae has progressively developed resistance to sulfonamides, penicillin, tetracycline and fluoroquinolones, and gonococcal susceptibility to cephalosporins has been declining worldwide. Methods: We described trends in gonococcal antimicrobial susceptibility in the USA from January 2006 through June 2012. Susceptibility data for cefixime, ceftriaxone, azithromycin, penicillin, tetracycline and ciprofloxacin were obtained from the Gonococcal Isolate Surveillance Project (GISP), a sentinel surveillance system that monitors antimicrobial susceptibility in urethral gonococcal isolates collected from symptomatic men at 25–30 sexually transmitted disease clinics throughout the USA. Results: The percentage of isolates with elevated cefixime minimum inhibitory concentrations (MICs) (≥0.25 µg/mL) increased from 0.1% in 2006 to 1.4% in 2010–2011 and was 1.1% in the first 6 months of 2012. The percentage with elevated ceftriaxone MICs (≥0.125 µg/mL) increased from 0.1% in 2006 to 0.3%–0.4% during 2009 through the first 6 months of 2012. There were no temporal trends in the prevalence of elevated azithromycin MICs (≥2 µg/mL) (0.2%–0.5%). The prevalence of resistance remained high for penicillin (11.2%–13.2%), tetracycline (16.7%–22.8%) and ciprofloxacin (9.6%–14.8%). Conclusions: The proportion of gonococcal isolates with elevated cephalosporin MICs increased from 2006 to 2010, but plateaued during 2011 and the first 6 months of 2012. Resistance to previously recommended antimicrobials has persisted. As the number of antimicrobials available for gonorrhoea treatment dwindles, surveillance systems such as GISP will be critical to detect emerging resistance trends and guide treatment decisions.